2013
DOI: 10.1155/2013/368970
|View full text |Cite
|
Sign up to set email alerts
|

Omentin-1 Stimulates Human Osteoblast Proliferation through PI3K/Akt Signal Pathway

Abstract: It has been presumed that adipokines deriving from adipose tissue may play important roles in bone metabolism. Omentin-1, a novel adipokine, which is selectively expressed in visceral adipose tissue, has been reported to stimulate proliferation and inhibit differentiation of mouse osteoblast. However, little information refers to the effect of omentin-1 on human osteoblast (hOB) proliferation. The current study examined the potential effects of omentin-1 on proliferation in hOB and the signal pathway involved.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 40 publications
(48 reference statements)
0
57
0
3
Order By: Relevance
“…Because studies suggest that the majority of colorectal cancer cases arise through chromosomal instability (36), this pathway could provide a plausible link; however, the exact initiating mechanisms and relationship with tumor progression are still to be elucidated. Novel data have also implicated omentin in the Akt phosphorylation/activation signaling pathways (16,17). PI3K activity is known to be associated with the transforming activity of viral oncogenes (37) and to trigger a cascade of tumorigenic responses, from cell growth and proliferation to survival and motility (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because studies suggest that the majority of colorectal cancer cases arise through chromosomal instability (36), this pathway could provide a plausible link; however, the exact initiating mechanisms and relationship with tumor progression are still to be elucidated. Novel data have also implicated omentin in the Akt phosphorylation/activation signaling pathways (16,17). PI3K activity is known to be associated with the transforming activity of viral oncogenes (37) and to trigger a cascade of tumorigenic responses, from cell growth and proliferation to survival and motility (38).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying regulatory mechanisms mediating omentin dysregulation in obesity are unknown, but could potentially include adipocyte hypertrophy, inflammation, and oxidative stress, as well as a failure of transcriptional regulation. Conversely, in cancer models omentin was suggested to promote cancer cell growth via triggering genomic instability (15) and PI3K/Akt (phosphatidylinositol-3 kinase downstream effector) signaling pathways (16,17). These cancer-promoting effects of omentin have been described independent of its abilities to regulate obesity-induced metabolic risk (18).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that omentin 1 stimulates the release of OPG and hampers the production of RANKL in osteoblasts through the signalling pathway PI3K-Akt in vitro (23). Moreover, results showed that omentin 1 hampers differentiation of osteoblasts, which may be an effect from the hampered expression of osteocalcin and bone matrix mineralization.…”
Section: Discussionmentioning
confidence: 97%
“…It also induces human osteoblast proliferation -most probably through the PI3K/Akt signal pathway [31]. In the co-culture system of osteoblasts and osteoclasts precursors, omentin-1 also reduced osteoclasts formation by stimulating OPG and inhibiting RANKL production in osteoblasts [7,8].…”
Section: Prace Oryginalnementioning
confidence: 99%